Synthesis, Characterization and Quantum Chemical Studies of Inhibition Ability of Novel 5-Nitro Isatin Derivatives on The Corrosion of Carbon Steel in Sea Water - Kubba, Rehab M.; Ahmed, Athraa H.; Al-Majidi, Suaad M. H. (Iraqi Journal of Science, 2019)
This research includes synthesis of new 5-Nitro isatin derivatives starting from 5-Nitro-3-(ethyl imino acetate)-2-oxo indole (1) namely 5-nitro-3-[(imino acetyl) semicarbazide]-2-oxo indole (2); 5-nitro-3-[(imino acetyl) phenylsemicarbazide]-2-oxo indole (3); 5-nitro-3-[(imino acetyl) thiosemicarbazide]-2-oxo indole (4); 5-nitro-3-[(iminoacetyl) phenylthiosemi carbazide]-2-oxo indole (5); 5-nitro-3-[(methyl imino)-4H-1, 2, 4-triazol-5-ol-3-yl]-2-oxo indole (6); 5-nitro-3-[(methyl imino) 4-phenyl-1, 2, 4-triazol-5-ol-3-yl]-2-oxo indole (7); 5-nitro-3-[(methyl imino) 4-phenyl-1, 2, 4-triazol-5-thiol-3-yl]-2-oxo indole (8) and 5-nitro-3-[(methyl imino) 4H-1, 2, 4-triazol-5-thiol-3-yl]-2-oxo indole (9). The derivatives were characterized using FTIR, 1HNMR, 13CNMR and C.H.N.S analysis with the measurement of some physical properties. Quantum mechanical method of the Density Functional Theory (DFT) of B3LYP with a level of 6-311++G (2d, 2p) were used to calculate the geometrical structure, physical properties, and inhibition efficiency parameters, at the equilibrium geometry in four media (vacuum, DMSO, ETOH and H2O). The theoretical results showed that compound (7) was the best corrosion inhibitor among the others. Finally, potentiodynamic polarization studies showed that the compound (7) was a mixed type inhibitor. The adsorption of this compound on a carbon steel surface from sea water obeyed the Langmuir adsorption isotherm. The decrease in the inhibition efficiency with the increase in temperature and the low negative values of Î”HÂ°ads suggest predominant physisorption of the prepared compound (7) on the carbon steel surface. The surface morphology of the carbon steel before and after inhibition was studied using SEM (Scanning Electron Microscopy) and AFM (Atomic Force Microscopy) techniques.